ALK-Negative Primary Cutaneous Anaplastic Large Cell Lymphoma With Systemic Involvement or Systemic ALCL With Cutaneous Lesion. A Diagnostic Dilemma. (1st May 2022) - Gupta, Ishan; Ramteke, Prashant; Narwal, Anubhav; Sharma, Mehar Chand; Bakhshi, Sameer; Mallick, Saumyaranjan
Abstract: Primary cutaneous anaplastic large-cell lymphoma (C-ALCL) is a cutaneous CD30-positive lymphoproliferative disorder. The patients usually present with single or multiple cutaneous nodules or papules and about 10% cases present with extracutaneous manifestations, which are predominantly in the form of regional lymph nodal involvement. Visceral involvement especially pulmonary or hepatic involvement in C-ALCL is only rarely described in the scientific literature. Approximately 20%–42% cases show spontaneous regression, about 50% cases may recur; however, C-ALCL generally carries a good prognosis. We present a rare case of primary C-ALCL in a 66-year-old man with regional lymph nodal and hepatic involvement. Differential diagnostic entities are discussed in this report with the review of the literature.